Educación familiar - Campaña Madril, Dayra Gissela (2016)
The family as the first educational area needs to reflect on their educational patterns and become aware of their role in the education of their children. The complexity of the current flee reality of his hands and this affects the child's life, leading family that arise in everyday reality and school problems: lack of interest, lack of motivation, dependence, poor performance , school failure , violence, among others. With this research project was pretend understand the causes of child abuse and its impact on the academic performance of children in the Second Year of Basic Education "A" from Education Unit " Narciso Cerda Maldonado" from La Mana, Cotopaxi province, causing complex problems in society. For the realization of this research has taken as reference the realization of a diagnosis through observation students and surveys of the educational community , determining that the academic performance of students is insufficient particularly those which are suffering child abuse , why is feasible to implement a guide family educational practices aimed at parents and teachers to improve the role of parents in the integral formation of dicent using strategies as meet people who have experienced this type of problem and who overcame the aftermath, through socialization workshops to achieve make aware and experiences in families who are suffering child abuse , benefiting 800 people, including students , teachers and families ; will strengthen family relationships reduce child abuse and improve the academic performance of the aforementioned educational community.